Oxidation properties and thermal hazard of pinane - Haijun Cheng; Haoping Chen; Qilin Huang; Qiaoni Luo; Min Liang; Suyi Dai; Fang Lai; Li Ma; Weiguang Li; Xiongmin Liu (Case Studies in Thermal Engineering, 2023)
Although pinane has a wide range of uses, there are no reports on the safety of pinane oxidation. The thermal oxidation properties of pinane were investigated through MCPVT. The primary oxidation products of pinane were separated and structurally characterised, and its decomposition properties were assessed by MCPVT and DSC. The results showed that pinane had an initial oxygen uptake temperature of 123.5 °C and exploded when the temperature rose to 132.7 °C. Pinane autoxidised at 110 °C for 9 h formed a high level of peroxide (81.18 mmol/kg) with an activation energy of 138.77 kJ/mol. The oxidation of pinane occurs mainly at the tertiary carbon atom attached to the methyl group, and the main peroxide produced is pinane hydroperoxide (PHP). PHP has an exothermic onset temperature (Tonset), a heat of decomposition (QDSC) and an activation energy of decomposition of 114.6 °C, 1878.0 J/g and 109.4 kJ/mol respectively, which should classify it as a hazardous substance. PHP has a lower activation energy than pinane and is the determining factor for the safety of the pinane oxidation reaction. The products of thermal runaway of pinane are relatively complex and consist mainly of 1-(2, 2-dimethyl-3-ethylcyclobutyl) ethanone, nopinone, 2, 3-pinanediol and pinonic acid.